Comparison of central versus peripheral delivery of pregabalin in neuropathic pain states - Martinez Jose A; Kasamatsu Manami; Rosales-Hernandez Alma; Hanson Leah R; Frey William H; Toth Cory C (SAGE Publishing, 2012)
Abstract Background Although pregabalin therapy is beneficial for neuropathic pain (NeP) by targeting the CaVα2δ-1 subunit, its site of action is uncertain. Direct targeting of the central nervous system may be beneficial for the avoidance of systemic side effects. Results We used intranasal, intrathecal, and near-nerve chamber forms of delivery of varying concentrations of pregabalin or saline delivered over 14 days in rat models of experimental diabetic peripheral neuropathy and spinal nerve ligation. As well, radiolabelled pregabalin was administered to determine localization with different deliveries. We evaluated tactile allodynia and thermal hyperalgesia at multiple time points, and then analyzed harvested nervous system tissues for molecular and immunohistochemical changes in CaVα2δ-1 protein expression. Both intrathecal and intranasal pregabalin administration at high concentrations relieved NeP behaviors, while near-nerve pregabalin delivery had no effect. NeP was associated with upregulation of CACNA2D1 mRNA and CaVα2δ-1 protein within peripheral nerve, dorsal root ganglia (DRG), and dorsal spinal cord, but not brain. Pregabalin's effect was limited to suppression of CaVα2δ-1 protein (but not CACNA2D1 mRNA) expression at the spinal dorsal horn in neuropathic pain states. Dorsal root ligation prevented CaVα2δ-1 protein trafficking anterograde from the dorsal root ganglia to the dorsal horn after neuropathic pain initiation. Conclusions Either intranasal or intrathecal pregabalin relieves neuropathic pain behaviours, perhaps due to pregabalin's effect upon anterograde CaVα2δ-1 protein trafficking from the DRG to the dorsal horn. Intranasal delivery of agents such as pregabalin may be an attractive alternative to systemic therapy for management of neuropathic pain states.